2014
DOI: 10.1002/chem.201404863
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine–BODIPY–Fullerene Triads as Photosynthetic Reaction Center Models: Substitution and Solvent Polarity Effects on Photoinduced Charge Separation and Recombination

Abstract: Novel photosynthetic reaction center model compounds of the type donor2 -donor1 -acceptor, composed of phenothiazine, BF2 -chelated dipyrromethene (BODIPY), and fullerene, respectively, have been newly synthesized using multistep synthetic methods. X-ray structures of three of the phenothiazine-BODIPY intermediate compounds have been solved to visualize the substitution effect caused by the phenothiazine on the BODIPY macrocycle. Optical absorption and emission, computational, and differential pulse voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 85 publications
1
65
1
Order By: Relevance
“…Electrochemical studies:c yclic voltammograms and the Gibbs free-energy changes of the charge separation/charge recombination To confirmt he possibility of photoinduced electron transfer (PET), the electrochemical properties of the dyads were studied ( Figure 3). [26,28,[63][64][65][66] Twor eversible oxidation waves at + 0.58 and + 1.04 Vw ere recorded for NDI,a nd two reversible reduction waves were recorded at À1.45 and À1.82 V. For TEMPO, a reversible oxidation wave at + 0.32 Vw as observed. According to the oxidation and reduction potentials of the reference compounds, we anticipate an electron transfer from the TEMPOm oiety to the NDI moiety.F or NDI-TEMPO,t he first oxidationp otential is at + 0.41 V, which corresponds to the TEMPOm oiety,a nd the first reduction potential is at À1.41 V, which is attributedt ot he NDIm oiety.T he standard free energy of the charge-transfer reaction, DG CS 8,i nNDI-TEMPO was calculated by using the Rehm-Weller equations [Eqs.…”
Section: Uv/vis Absorption and Fluorescencespectramentioning
confidence: 85%
See 1 more Smart Citation
“…Electrochemical studies:c yclic voltammograms and the Gibbs free-energy changes of the charge separation/charge recombination To confirmt he possibility of photoinduced electron transfer (PET), the electrochemical properties of the dyads were studied ( Figure 3). [26,28,[63][64][65][66] Twor eversible oxidation waves at + 0.58 and + 1.04 Vw ere recorded for NDI,a nd two reversible reduction waves were recorded at À1.45 and À1.82 V. For TEMPO, a reversible oxidation wave at + 0.32 Vw as observed. According to the oxidation and reduction potentials of the reference compounds, we anticipate an electron transfer from the TEMPOm oiety to the NDI moiety.F or NDI-TEMPO,t he first oxidationp otential is at + 0.41 V, which corresponds to the TEMPOm oiety,a nd the first reduction potential is at À1.41 V, which is attributedt ot he NDIm oiety.T he standard free energy of the charge-transfer reaction, DG CS 8,i nNDI-TEMPO was calculated by using the Rehm-Weller equations [Eqs.…”
Section: Uv/vis Absorption and Fluorescencespectramentioning
confidence: 85%
“…To confirm the possibility of photoinduced electron transfer (PET), the electrochemical properties of the dyads were studied (Figure ) . Two reversible oxidation waves at +0.58 and +1.04 V were recorded for NDI , and two reversible reduction waves were recorded at −1.45 and −1.82 V. For TEMPO, a reversible oxidation wave at +0.32 V was observed.…”
Section: Resultsmentioning
confidence: 99%
“…BODIPY* produced by excitation could undergo inter system crossing (ISC) to populate 3 BODIPY* (~1.76 eV),[54] alternatively it could undergo electron transfer to produce PTZ •+ -BODIPY •─ [50]. E0-0, energy due to 0-0 electronic transition, of BODIPY moiety of dyads was found to be ~ 2.44 eV (estimated from intersecting wavelength of the…”
mentioning
confidence: 99%
“…Some of these include, the photosynthetic antennacenter mimic involving BODIPY as energy funnelling entity to porphyrazine and PTZ as a sacrificial electron donor, [47] chiral BODIPY and aza-BODIPY-based D--A conjugated polymers involving PTZ as electron donor, [48,49] Recently, D'Souza et al has reported PTZ-BODIPY-C60 triads as photosynthetic reaction center models and studied the effect of solvents and the substitution on the photo-induced charge separation and recombination. [50] However, the study was limited to only two dyads i.e., PTZ connected to BODIPY either directly (no spacer) or via phenyl bridge and comprehensive photo-induced electron transfer studies w.r.t. the spacer size and type were not presented.…”
mentioning
confidence: 99%
“…Perusal of the literature revealed interesting reports on covalently linked, strongly coupled BODIPY oligomers, but reports on multi‐BODIPY systems based on 3‐pyrrolyl BODIPYs are scarce because of the unavailability of appropriate functionalized 3‐pyrrolyl BODIPYs. In continuation of our work on 3‐pyrrolyl BODIPYs, herein we report the synthesis of and studies on covalently linked BODIPY oligomers 1 – 3 based on 3‐pyrrolyl BODIPY. Our aim was to prepare appropriately functionalized 3‐pyrrolyl BODIPYs that can be used as building blocks to synthesize covalently linked BODIPY oligomers.…”
Section: Introductionmentioning
confidence: 99%